Post-modification of 2-formylthiophene based heterocyclic azo dyes. (October 2016) - Xu, Dan; Li, Zhu; Peng, Yu-Xin; Geng, Jiao; Qian, Hui-Fen; Huang, Wei
Abstract: In order to further adjust the π -conjugated system, solubility and electronic spectrum of 2-amino-3-cyano-4-chloro-5-formylthiophene based blue colored heterocyclic blue azo dyes, a post-modification strategy has been used to extend their terminal aldehyde radical into either an imine, acetal or α, β -unsaturated cyanoacetic ester group. The resultant azo-azomethine dyes exhibit slight bathochromic shifts in their UV–Vis spectra with the increase of the π -conjugated system. In contrast, acetal terminated products display good solubility in organic solvents but hypsochromic shifts in their UV–Vis spectra. It is worth mentioning that the α, β -unsaturated cyanoacetic ester derivatives show significant bathochromic shifts and improvement of solubility simultaneously originating from the presence of increased π -conjugated system as well as the terminal cyano and ester groups. It is believed that the current study could provide a practical post-modification strategy for decorating and improving the dyeing performance of certain dyes with functional end groups. Graphical abstract: A post-modification strategy has been achieved for 2-amino-3-cyano-4-chloro-5-formylthiophene based heterocyclic blue azo dyes with the common terminal aldehyde group, where an α, β -unsaturated cyanoacetic ester derivative shows the largest bathochromic shift of 87 nm and improvement of solubility simultaneously. Highlights: Three sets of novel post-modification S -containing heterocyclic azo dyes are described. Representative crystal structures for every series are obtained and compared. Variation of π -conjugated length and polarity shows different λ max and solvatochromism. An α, β -unsaturated cyanoacetic ester has the largest bathochromic shift of 87 nm.